Dakwah Bil Hal: Implementasi Nilai Amanah dalam Organisasi Pengelola Zakat untuk Mengurangi Kesenjangan dan Kemiskinan - Hakim, Rahmad (Iqtishodia: Jurnal Ekonomi Syariah, 2017)
Da???wah in Islam has the meaning of calling for goodness and forbidding the badness, but the most effective method is actually da???wah bil hal. Nowadays, where the number inequality and poverty is increased, da???wah bil hal is strongly needed, not least for the zakah organization. This organization has an important role in reducing the number of inequality and poverty because it???s an intermediary function between donators (muzakki) and users (mustahik). The absence of amanah in zakat management organization at least has an impact on two things; first, the lack of public awareness related to zakat and the willingnes to pay for zakat. Second, the number of donors (muzakki) distributes zakat individually, so the impact of zakat is ineffective. Using the literature approach, this paper tries to discuss the importance of amanah value as an instrument of da???wah bil hal. It can be concluded that amanah value in zakah management can be implemented to reduce the number of inequality and poverty through several important dimensions, namely: mentality, accountability, capability, professional and the right to target. Keywords: da???wah bil hal, zakah management, amanah.